Proteoglycan abnormalities in olfactory epithelium tissue from subjects diagnosed with schizophrenia - Pantazopoulos, Harry; Boyer-Boiteau, Anne; Holbrook, Eric H.; Jang, Woochan; Hahn, Chang-Gyu; Arnold, Steven E.; Berretta, Sabina (Schizophrenia research, 2013)
Emerging evidence points to proteoglycan abnormalities in the pathophysiology of schizophrenia (SZ). In particular, markedly abnormal expression of chondroitin sulfate proteoglycans (CSPGs), key components of the extracellular matrix, was observed in the medial temporal lobe. CSPG functions, including regulation of neuronal differentiation and migration, are highly relevant to the pathophysiology of SZ. CSPGs may exert similar functions in the olfactory epithelium (OE), a continuously regenerating neural tissue that shows cell and molecular abnormalities in SZ. We tested the hypothesis that CSPG expression in OE may be altered in SZ. CSPG-positive cells in postmortem OE from non-psychiatric control (n=9) and SZ (n=10) subjects were counted using computer-assisted light microscopy. ‘Cytoplasmic’ CSPG (c-CSPG) labeling was detected in sustentacular cells and some olfactory receptor neurons (c-CSPG+ORNs), while ‘pericellular’ CSPG (p-CSPG) labeling was found in basal cells and some ORNs (p-CSPG+ORNs). Dual labeling for CSPG and markers for mature and immature ORNs suggests that c-CSPG+ORNs correspond to mature ORNs, and p-CSPG+ORNs to immature ORNs. Previous studies in the same cohort demonstrated that densities of mature ORNs were unaltered (Arnold et al., 2001). In the present study, numerical densities of c-CSPG+ORNs were significantly decreased in SZ (p<0.025; 99.32% decrease), suggesting a reduction of CSPG expression in mature ORNs. Previous studies showed a striking increase in the ratios of immature neurons with respect to basal cells. In this study, we find that the ratio of p-CSPG+ORNs/CSPG+basal cells was significantly increased (p=0.03) in SZ, while numerical density changes of p-CSPG+ORNs (110.71% increase) or CSPG+basal cells (53.71% decrease), did not reach statistical significance. Together, these results indicate that CSPG abnormalities are present in the OE of SZ and specifically point to a reduction of CSPG expression in mature ORNs in SZ. Given the role CSPGs play in OE cell differentiation and axon guidance, we suggest that altered CSPG expression may contribute to ORN lineage dysregulation, and olfactory identification abnormalities, observed in SZ.